INSIDER ATTACKER DETECTION IN WIRELESS SENSOR NETWORK - V., Satheeswaran (International Journal of Psychosocial Rehabilitation, 2017)
Wireless Sensor Network (WSN) is an emerging technology that shows great promise for various futuristic applications both for mass public and military. The sensing technology combined with processing power and wireless communication makes it lucrative for being exploited in abundance in future. Wireless sensor networks are characterized by severely constrained computational and energy resources, and an ad hoc operational environment. The Wireless sensor networks are challenged by much type of attacks like Spoofed, altered, or replayed routing Information, Selective forwarding, Sybil attacks, Wormholes, and HELLO flood. Packet dropping and modification are common attacks that can be launched by an adversary to disrupt communication in wireless multi-hop sensor networks. Many schemes have been proposed to mitigate or tolerate such attacks but very few can effectively and efficiently identify the intruders. To address this problem, we propose a simple yet effective scheme, which can identify misbehaving forwarders that drop or modify packets. The scheme uses many powerful algorithms in every rounds of the packet modifier or dropper identification. Extensive analysis and simulations have been conducted to verify the effectiveness and efficiency of the scheme.